Syntheses, structures and photocatalytic properties of a series of cobalt coordination polymers based on flexible bis(triazole) and dicarboxylate ligands. (10th January 2017) - Zhao, Shan; Zheng, Tian-Rui; Zhang, Ya-Qian; Lv, Xiu-Xiu; Li, Bao-Long; Zhang, Yong
Graphical abstract: Seven cobalt(II) coordination polymers based on 1, 2-bis(1, 2, 4-triazol-1-ylmethyl)benzene and dicarboxylate were synthesized and characterized which are effective photocatalytic catalysts for the degradation of methyl orange. Abstract: Seven cobalt(II) coordination polymers [Co(obtz)(Meip)] n (1 ), [Co(obtz)(ip)] n (2 ), [Co2 (obtz)2 (tdc)2 (H2 O)]·2H2 O n (3 ), [Co(obtz)(1, 4-bdc)(H2 O)] n (4 ), [Co(obtz)(adc)] n (5 ), [Co(obtz)2 (fum)]·2H2 O n (6 ) and [Co(obtz)(hip)] n (7 ) (obtz = 1, 2-bis(1, 2, 4-triazole-1-ylmethyl)benzene, Meip = 5-methylisophthalate, ip = isophthalate, tdc = 2.5-thiophenedicarboxylate, 1, 4-bdc = 1, 4-benzenedicarboxylate, adc = 1, 3-adamantanedicarboxylate, fum = fumarate, hip = 5-hydroxyisophthalate) were synthesized.1 shows a (3, 4)-connected 2D network with the point symbol of (3·8 2 )(3 2 ·4·8 2 ·9).2 exhibits a (3, 5)-connected 2D network with the point symbol of (4 2 ·6)(4 2 ·6 6 ·8 2 ).3 presents a (3, 6)-connected 2D network with the point symbol of (3·4·6)(3 2 ·4 4 ·5 4 ·6 3 ·7·8).4 and5 exhibit unusual 2D → 2D polycatenated network based on 2D sql network.6 shows a 2D sql network.7 presents the ladder-like 1D chain with side arms. The diverse structures demonstrate that the structures of coordination polymers can be tuned by the dicarboxylate and bis(triazole) co-ligands. The thermal stability of1 –7 was investigated.1 –7 are effective photocatalytic catalysts for the degradation of methyl orange.